2017
DOI: 10.1063/1.5005009
|View full text |Cite
|
Sign up to set email alerts
|

Core losses of a permanent magnet synchronous motor with an amorphous stator core under inverter and sinusoidal excitations

Abstract: We report core loss properties of permanent magnet synchronous motors (PMSM) with amorphous magnetic materials (AMM) core under inverter and sinusoidal excitations. To discuss the core loss properties of AMM core, a comparison with non-oriented (NO) core is also performed. In addition, based on both experiments and numerical simulations, we estimate higher (time and space) harmonic components of the core losses under inverter and sinusoidal excitations. The core losses of PMSM are reduced by about 59% using AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…See Refs. 2,12,14,15) for the details of design and fabrication process of rotor and stator cores. Figure 3 shows the schematic of the PMSM and its control system under no-load condition.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…See Refs. 2,12,14,15) for the details of design and fabrication process of rotor and stator cores. Figure 3 shows the schematic of the PMSM and its control system under no-load condition.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The losses in the driving electric motors mainly consist of mechanical, copper, and core losses (iron losses). Recently, in order to reduce core losses of the motors, the motors based on core with amorphous magnetic materials (AMM) [1][2][3][4][5][6][7][8][9][10][11][12] and nanocrystalline magnetic materials (NMM) [13][14][15] have been developed and examined. NMM and AMM exhibit lower iron loss 16) than nonoriented (NO) silicon steel sheets.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PWM inverter outputs have higher harmonic components superimposed in fundamental waveforms. Many studies have reported that, due to high harmonic components, iron loss of the motor core under PWM inverter excitation increases [7][8][9][10][11][12][13][14][15][16][17] by 10%-50% 10) compared with sinusoidal excitation. In these researches, magnetic hysteresis loops had many minor loops.…”
Section: Introductionmentioning
confidence: 99%